Resolution of a paradox: Hummingbird flight at high elevation does not come without a cost - Altshuler, Douglas L. (National Academy of Sciences, 2004)
Flight at high elevation is energetically demanding because of parallel reductions in air density and oxygen availability. The hovering flight of hummingbirds is one of the most energetically expensive forms of animal locomotion, but hummingbirds are nonetheless abundant at high elevations throughout the Americas. Two mechanisms enhance aerodynamic performance in high-elevation hummingbirds: increase in wing size and wing stroke amplitude during hovering. How do these changes in morphology, kinematics, and physical properties of air combine to influence the aerodynamic power requirements of flight across elevations? Here, we present data on the flight performance of 43 Andean hummingbird species as well as a 76-taxon multilocus molecular phylogeny that served as the historical framework for comparative analyses. Along a 4,000-m elevational transect, hummingbird body mass increased systematically, placing further aerodynamic demands on high-elevation taxa. However, we found that the minimum power requirements for hovering flight remain constant with respect to elevation because hummingbirds compensate sufficiently through increases in wing size and stroke amplitude. Thus, high-elevation hummingbirds are not limited in their capacity for hovering flight despite the challenges imposed by hypobaric environments. Other flight modes including vertical ascent and fast forward flight are more mechanically and energetically demanding, and we accordingly also tested for the maximum power available to hummingbirds by using a load-lifting assay. In contrast to hovering, excess power availability decreased substantially across elevations, thereby reducing the biomechanical potential for more complex flight such as competitive and escape maneuvers.